Business Intelligence for Academic Management Systems: Results of a Study in a Brazilian Federal University - Vieira, Alana R. R.; Seabra, Rodrigo D.; Garcés, Lina (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Brazilian public universities require managing vast and diverse academic and administrative information. The government requires periodic reports about finances, education, research, and social impact to obtain enough economic resources for universities’ continuous operations. Additionally, since the approval of the National Law nº 12.527 (LAI - Lei de Acesso à Informação) of 2012, all public organizations must provide information as requested by any civilian, public, or private organization. Problem: Answering diverse information requests by public universities demands a lot of time and effort from public officials since, to produce a report, they must consult different systems and documents. These tasks increase the workload of public employees, which is repetitive and manual work. Solution: This work investigates the information necessities of public universities in Brazil to manage their academic sectors strategically, using Business Intelligence (BI) techniques. IS Theory: This work was developed using organizational information processing theory, which helps to understand how information is processed and exchanged within organizations and among their members. Method: Observations and semi-structured interviews were conducted with experts working in a public university’s academic sector. The interviews were transcripted, and topic analysis was conducted to identify necessary functional and non-functional requirements. Results: Requirements were specified using the Personas method, containing stakeholders’ needs, motivations, and goals for using a BI solution. Moreover, the required structured, semi-structured, and non-structured data to support operational, managerial, and strategic activities in the academic sector were identified. A preliminary conceptual model of the BI solution is also proposed. Additionally, important data integrations among university sectors were defined. Contributions: The results of this study are hoped to be used as an asset to define a BI solution to support academic management in Brazilian public universities. As a future work, it is intended to develop an initial BI tool and create a national reference architecture to guide the development of these solutions.